Saliva: nervous control, composition and function - Regis André Ticona Vidal (2021)
The nervous control of salivary secretion is exclusive to the autonomic nervous system, which has a sympathetic part, which originates from the thoracic segments; and a parasympathetic, which occurs through nerve signals from the salivary nuclei. Nerve control begins with gustatory stimuli, which are mediated by NCV3 (third branch of the trigeminal nerve), NC VII (facial nerve), and NCIX (glosopharyngeal nerve). In addition, the pathway that follows the stimulation for salivary secretion is: preganglionary fibers, ganglion, and fibers postanglionary parasympathetic fibers. Saliva is composed of 95 to 99 % water and the remaining percentage corresponds to solids that are subdivided into organic, where protein compounds such as enzymes and immunoglobulins are found; non-protein such as urea and inorganic compounds that behave as electrolytes. In addition, due to its composition, it fulfils functions related to oral health and phonation.